2006
DOI: 10.1256/qj.04.152
|View full text |Cite
|
Sign up to set email alerts
|

Equatorial waves in the lower stratosphere. I: A novel detection method

Abstract: SUMMARYWavenumber-frequency spectral analysis and linear wave theory are combined in a novel method to quantitatively estimate equatorial wave activity in the tropical lower stratosphere. The method requires temperature and velocity observations that are regularly spaced in latitude, longitude and time; it is therefore applied to the ECMWF 15-year re-analysis dataset (ERA-15). Signals consistent with idealized Kelvin and Rossby-gravity waves are found at wavenumbers and frequencies in agreement with previous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 38 publications
(34 reference statements)
3
26
0
Order By: Relevance
“…Kelvin waves are the most prominent global scale equatorially trapped wave mode in atmospheric temperatures (e.g., Tindall et al, 2006a). They are symmetric with respect to the equator, trapped at latitudes between about 20 • S and 20 • N in the stratosphere and travel eastward.…”
Section: Introductionmentioning
confidence: 99%
“…Kelvin waves are the most prominent global scale equatorially trapped wave mode in atmospheric temperatures (e.g., Tindall et al, 2006a). They are symmetric with respect to the equator, trapped at latitudes between about 20 • S and 20 • N in the stratosphere and travel eastward.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature field of Kelvin waves is in the symmetric mode (Andrews et al, 1987;Tindall et al, 2006), and according to the dispersion relation (Ern and Preusse, 2009;Matsuno, 1966), Kelvin wave components with different wave numbers and frequencies are extracted from the symmetric spectra by band pass filtering. The filtering region of Kelvin wave in the spectra is recognized by the different equivalent depth (Wheeler and Kiladis, 1999), corresponding to different phase speed of Kelvin waves (c x = √ gh e , where g is the gravitational acceleration).…”
Section: Extraction Of Kelvin Wavesmentioning
confidence: 99%
“…They are eastward propagating equatorial waves excited by tropical convection (Bergman and Salby, 1994), and are the most prominent components of the equatorially trapped wave mode of the temperature field (Tindall et al, 2006;Ern et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Kelvin waves dominate sub-seasonal variability in the tropical tropopause region (Tindall et al, 2006;Kim and Son, 2012). They modulate the height and temperature of the tropical tropopause (Tsuda et al, 1994;Shimizu and Tsuda, 1997) and were found to be important for cirrus formation (Boehm and Verlinde, 2000;Immler et al, 2008;Suzuki et al, 2013) and dehydration of air entering the lower stratosphere (Fujiwara et al, 2001).…”
mentioning
confidence: 99%
“…Equatorial atmospheric waves have been investigated using satellite data from Nimbus-7 LIMS (Limb Infrared Monitor of the Stratosphere; Salby et al, 1984), the Microwave Limb Sounder (MLS; Mote et al, 2002), SABER (Sounding of the Atmosphere using Broadband Emission Radiometry; Ern et al, 2008;Ern and Preusse, 2009), and High Resolution Dynamics Limb Sounder (HIRDLS; Alexander and Ortland, 2010). Furthermore, several studies on atmospheric Kelvin waves are based on analysis or reanalysis data from numerical weather prediction (NWP) centers (Tindall et al, 2006;Suzuki and Shiotani, 2008;Suzuki et al, 2010;Fujiwara et al, 2012;Flannaghan and Fueglistaler, 2013).…”
mentioning
confidence: 99%